2022
DOI: 10.3389/fpubh.2022.917732
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Cost-Effectiveness of Inactivated Vaccine to Address COVID-19 Pandemic in China: Evidence From Randomized Control Trials and Real-World Studies

Abstract: ObjectiveThis study aimed to determine the efficacy, effectiveness, and cost-effectiveness of inactivated COVID-19 vaccines (CoronaVac and BBIBP-CorV) in China using existing international clinical trials and real-world evidence.MethodsThrough a search of PubMed, Embase, Web of Science, and CNKI, studies investigating the effectiveness of inactivated COVID-19 vaccines were identified, and a meta-analysis was undertaken to synthesize the vaccine efficacy and effectiveness data. Moreover, a decision-analytic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
(86 reference statements)
1
25
0
Order By: Relevance
“…In our study, the VE against hospitalization was 75.7%, which is lower than the 100% reported in clinical trials for preventing COVID-19-related hospitalization and severe infection ( Al Kaabi et al, 2021 ; Tanriover et al, 2021 ). However, this finding is consistent with a recent meta-analysis of nine real-world studies that reported the pooled effectiveness of inactivated vaccines to be 79.10% (95% CI: 71.69 to 86.51) ( Fu et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the VE against hospitalization was 75.7%, which is lower than the 100% reported in clinical trials for preventing COVID-19-related hospitalization and severe infection ( Al Kaabi et al, 2021 ; Tanriover et al, 2021 ). However, this finding is consistent with a recent meta-analysis of nine real-world studies that reported the pooled effectiveness of inactivated vaccines to be 79.10% (95% CI: 71.69 to 86.51) ( Fu et al, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…Inactivated virus vaccines such as BBIBP-CorV (Beijing Institute of Biological Products Co., Beijing, China) and CoronaVac (Sinovac Life Sciences, Beijing, China) have been widely used in China. 9 Our previous cross-sectional study revealed that early antibody responses were lower in patients with CHB than those in healthy controls (HCs) after the second dose of inactivated vaccines (primary vaccination, PV). 10 However, whether the third dose (booster) of inactivated vaccines is likely to improve antibody responses in patients with CHB is currently unknown.…”
Section: Introductionmentioning
confidence: 98%
“…To achieve the goal of herd immunity, a variety of vaccines have been introduced worldwide 35 . One of the main vaccines promoted in China is the inactivated virus vaccine, which has a high inoculation coverage among the population up to date 36 .…”
Section: Discussionmentioning
confidence: 99%